2019
DOI: 10.18357/jcs00019340
|View full text |Cite
|
Sign up to set email alerts
|

Planting Seeds: Fostering Preschool Children’s Interactions with Nature and Enhancing Intergenerational Relationships in a Campus Community Garden

Abstract: Children need nature. Nature is not optional; not a mere amenity, but rather, has important implications for children's health and well-being. Moreover, the natural environment is "essential infrastructure" to which all citizenry ought to have access. (Wells, Jimenez, & Martensson, 2018) Numerous research studies have found that children are increasingly disconnected from nature, choosing to spend much of their time indoors watching television and on computer screens (Hofferth, 2010;Louv, 2005;Rideout, Foehr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, in our study, the educational benefits of community gardens were the reason for the overwhelming support of the respondents, with community gardens allowing young children to experience planting activities and get close to nature. Previous studies have shown that community gardens foster young children's interaction with nature and strengthen intergenerational relationships (Gleeson, 2019) and that intergenerational interactions, in turn, promote sustainable community development. We also found that saving money by growing vegetables is the least important reason.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the educational benefits of community gardens were the reason for the overwhelming support of the respondents, with community gardens allowing young children to experience planting activities and get close to nature. Previous studies have shown that community gardens foster young children's interaction with nature and strengthen intergenerational relationships (Gleeson, 2019) and that intergenerational interactions, in turn, promote sustainable community development. We also found that saving money by growing vegetables is the least important reason.…”
Section: Discussionmentioning
confidence: 99%